Measurement of elastic backscattering differential cross sections for protons on natO in the energy range E= 4-6 MeV, suitable for EBS - Bosmpotinis, Konstantinos; Kokkoris, Michael; Lagoyannis, Anastasios; Taimpiri, Evangelia; Ziagkova, Anastasia (HNPS Advances in Nuclear Physics, 2022)
In this study we present the experimental cross sections of the natO(p,p0) elastic scattering, determined via the relative measurement technique, in the proton energy range Elab=4-6 MeV, at six backscattering detector angles between 120o and 170o, with a 10o step. The measurements were performed using the Van de Graaff Tandem 5.5 MV Accelerator of N.C.S.R. “Demokritos” in Athens, Greece and a high precision goniometer.